2004
DOI: 10.2166/wst.2004.0779
|View full text |Cite
|
Sign up to set email alerts
|

Activated Sludge Model No. 1 calibration for piggery wastewater treatment using respirometry

Abstract: To optimise the intermittent aeration process for piggery wastewater, the Activated Sludge Model No. 1 needs to be calibrated and adapted to this specific effluent. By combining aerobic and anoxic respirometric tests, biodegradation kinetics of organic fractions in piggery wastewater could be studied. Modeling of the respirometric curves proved that the simplified hydrolysis model was sufficient for piggery wastewater treatment simulation. The hydrolysis constant (K(H)) and heterotrophic sludge yield (Y(H)) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Firstly, default parameters taken from the literature (Henze et al, 2000;Hao et al, 2002;Boursier et al, 2004) were used for modelling. However, some modifications of the default parameters were necessary to fit the experimental results.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, default parameters taken from the literature (Henze et al, 2000;Hao et al, 2002;Boursier et al, 2004) were used for modelling. However, some modifications of the default parameters were necessary to fit the experimental results.…”
Section: Resultsmentioning
confidence: 99%
“…These models, however, are only relevant if simulation results truly represent behavior and performance of the process. Practical experience in nitrifying/denitrifying treatment plants over the last 10 years at Cemagref (France) has shown that even for the simplest IWA-type model (ASM1), the original default parameter values needed to be reconsidered to match predictions with measurements (Boursier et al, 2004;Choubert et al, 2005Choubert et al, , 2006Choubert et al, , 2008Lessard et al, 2007;Marquot et al, 2006;Stricker et al, 2003;Vigne et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…1 (ASM1) in late 80's , a substantial amount of information and experience has been gained from its application to a number of full-scale (mainly municipal) wastewater treatment plants (Coen et al, 1997;Wichern et al, 2001;Printemps et al, 2004). Due to recent developments, improvements and extensions of the models, their application for the simulation of treatment of industrial effluents has become increasingly feasible (Orhon, 1998;Barañao and Hall, 2004;Boursier et al, 2004).…”
Section: Introductionmentioning
confidence: 99%